Decay of Fc-dependent antibody functions after mild to moderate COVID-19 - Lee, Wen Shi; Selva, Kevin John; Davis, Samantha K.; Wines, Bruce D.; Reynaldi, Arnold; Esterbauer, Robyn; Kelly, Hannah G.; Haycroft, Ebene R.; Tan, Hyon-Xhi; Juno, Jennifer A.; Wheatley, Adam K.; Hogarth, P. Mark; et al. (Cell reports. Medicine, 2021)
The capacity of antibodies to engage with immune cells via the Fc region is important in preventing and controlling many infectious diseases. The evolution of such antibodies during convalescence from coronavirus disease 2019 (COVID-19) is largely unknown. We develop assays to measure Fc-dependent antibody functions against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S)-expressing cells in serial samples from subjects primarily with mild-moderate COVID-19 up to 149 days post-infection. We find that S-specific antibodies capable of engaging Fcγ receptors decay over time, with S-specific antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent phagocytosis (ADP) activity within plasma declining accordingly. Although there is significant decay in ADCC and ADP activity, they remain readily detectable in almost all subjects at the last time point studied (94%) in contrast with neutralization activity (70%). Although it remains unclear the degree to which Fc effector functions contribute to protection against SARS-CoV-2 re-infection, our results indicate that antibodies with Fc effector functions persist longer than neutralizing antibodies. [Display omitted] SARS-CoV-2 spike-specific Fc effector functions may contribute to COVID-19 controlSpike-specific ADCC and ADP responses decline in the 4 months post-infectionCompared to neutralization, ADCC and ADP are detectable longer post-infectionCross-reactive antibodies against human coronavirus spike increase post-infection Lee et al. report the decline of Fc-dependent antibody functions against SARS-CoV-2 spike in COVID-19 convalescent subjects up to 149 days post-infection. Unlike neutralization activity, plasma ADCC and ADP responses are sustained in the majority of subjects at the last time point measured.